Effective Marketing Strategies in Business: Trends and Best Practices in the Digital Age - Ricky Hermayanto (Jurnal Ad'ministrare, 2023)
This research aimed to explore effective marketing strategies in the digital era by identifying current trends and best practices. A qualitative research method was used, involving interviews with marketing experts and an analysis of case studies. The results show that a successful marketing strategy in the digital era involves a strong online presence, targeted advertising, and personalized communication with customers. Social media platforms were found to be crucial in reaching and engaging with customers. Additionally, content marketing, influencer marketing, and search engine optimization were identified as effective tactics. The research also highlights the importance of regularly updating and adapting marketing strategies to stay current with technological advancements and changing consumer behaviors. The findings of this research provide valuable insights for businesses looking to improve their marketing efforts in the digital era.